NOTARYS’ LIABILITY IN THE LEGALIZATION OF THE COPY OF IDENTITY CARD (KTP) UNDER THE ORIGINAL - Edwina Aileen Wirasasmita (NOTARIIL Jurnal Kenotariatan, 2018)
This study examines the notaries’ liability in a copy of Identity Card (KTP) legalization according to its original form. This is grounded on the rampant of the Identity Card Fraud cases and that notaries are authorized to approve a letter in compatibility with the original form as stated in the amended Law of the Republic of Indonesia Number 2 Year 2014 on Article 15 letter (d). To examine the phenomenon, the author used normative research method supported by interview as the instrument used to collect the data. The legal theories used are the theory of legal certainty, legal protection, and legal accountability. The results indicate that notary is responsible for parties who are disadvantaged due to the validation of the fake KTP card only in case if the notary endorsed the copy of the KTP without seeing and comparing the original form of it or the Notary has known that the KTP is a fake or not valid yet to endorse. On the contrary, a notary is not liable for having legalized an original KTP, not a photograph/photocopy, looking like original until it is unknown that it is actually a fake.